Immune-engineered H7N9 influenza hemagglutinin improves protection against viral influenza virus challenge - Hyesun Jang; Lauren M. Meyers; Christine Boyle; Anne S. De Groot; Lenny Moise; Ted M. Ross (Taylor & Francis Group, 2020)
The influenza hemagglutinin (HA) isolated from avian H7N9 influenza virus strains elicit weak immune responses. This low immunogenicity may be due to a regulatory T cell (Treg)-stimulating epitopes in HA from the H7N9 isolate A/Anhui/1/2013 (Anh/13). In this report, this Treg stimulating sequence was removed from the wild-type (WT) H7 HA amino acid sequence and replaced with a conserved CD4 + T cell stimulating sequences from human seasonal H3N2 strains and designed OPT1 H7 HA. The effectiveness of this optimized H7 HA protein was determined using a humanized mouse (HLA-DR3) expressing the human leukocyte antigen (HLA) DR3 allele. HLA-DR3 mice were pre-immunized by infecting with H3N2 influenza virus, A/Hong Kong/4108/2014 and then vaccinated intramuscularly with either the WT H7 HA from Anh/13 or the OPT1 H7 HA antigen without adjuvant. The OPT1 H7 HA vaccination group elicited higher H7 HA-specific IgG titers that resulted in a lower mortality, weight loss, and lung viral titer following lethal challenge with the H7N9 Anh/13 influenza virus compared to WT-vaccinated mice. Overall, T-cell epitope-engineered vaccines can improve the immunogenicity of H7 HA antigens resulting in enhanced survival and lower morbidity against H7N9 influenza virus challenge.